Detection method of lithium ion battery diaphragm
Through multi-stage infiltration detection, thermal pulse detection, temperature-infiltration alternating cycle detection and load-displacement detection, the problem of difficult to evaluate the stability of the microstructure and interface bonding firmness of the composite diaphragm in high-temperature and long-term cycle environments is solved, and high-precision detection and risk assessment of the composite diaphragm are achieved.
Patent Information
- Application Number
- CN202510363039.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing multi-dimensional network ceramic coating and polyvinyl film composite membrane are difficult to accurately evaluate the microstructure evolution and interface firmness of the interface under harsh working conditions such as high temperature and long-term cycles, and cannot meet the needs of high safety and high performance.
Multi-stage infiltration detection of the diaphragm is used to use at least two test solutions of different viscosity to obtain transmittance data and determine the infiltration hysteresis area; periodic thermal pulse detection is applied to the identified abnormal areas, temperature-time curve data is obtained and thermal diffusion abnormal areas are determined; strain data is obtained and microstructure change areas are determined through alternate cycle detection; load-displacement detection is performed on the microstructure change areas, interface combination energy data and channel resistance data are obtained and structural failure areas are determined; risk-level partitioning of the diaphragm is formed based on the structural failure areas to form application scenario adaptability evaluation data.
This method can accurately identify the microstructure changes and interface combination of composite diaphragms, effectively solving the problem that traditional detection methods are difficult to evaluate the stability of composite diaphragms in high temperature and long-term cycles, and meeting the needs of high safety and high performance.
Smart Images

Figure CN119881006A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery diaphragm detection, and in particular to a lithium ion battery diaphragm detection method. Background Art
[0002] The lithium-ion battery separator is an important functional component located between the positive and negative electrodes, which is used to block direct contact between electrons and allow lithium ions to shuttle freely. It is not only related to the cycle life, energy density and rate performance of the battery, but also plays a key protective role in safety; once the separator has problems such as heat shrinkage, pore blockage or interface peeling during use, the battery will face serious short circuit risks. At present, commonly used polyolefin separators such as polyethylene and polypropylene have good mechanical strength and low cost, but they are easy to shrink or melt at high temperatures and have limited ion transmission capacity. In order to improve safety and high energy density, the researchers introduced a multi-dimensional network ceramic coating (such as α-Al2O3) with a three-dimensional interconnected pore structure on the traditional polyolefin base membrane. 2 O 3 ) to enhance the heat resistance and ion transmission performance of the diaphragm, meeting the current higher demands of electric vehicles and large-scale energy storage systems for battery safety and performance.
[0003] However, the microstructure evolution and interface bonding stability of this multi-dimensional network ceramic layer and polyolefin base film composite diaphragm under harsh working conditions such as high temperature and long-term cycling are difficult to accurately evaluate through traditional detection methods. Although macroscopic detection (such as measuring thermal shrinkage, tensile strength or surface morphology) can find some problems, it is impossible to fully understand whether the three-dimensional network pores are blocked or collapsed, and it is difficult to quantify the bonding decay of the ceramic layer and the base film under multiple stresses (high temperature, vibration, electrochemical cycle). Especially in actual scenarios, when the battery needs to take into account both fast charging and discharging and high safety, the microscopic pore structure and interface stability of the diaphragm are crucial. Therefore, how to establish a high-precision detection method that can dynamically monitor and quantitatively characterize the changes in its microstructure for this type of composite diaphragm with both three-dimensional interconnected pores and multi-layer coupling characteristics at the interface has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] The main purpose of the present invention is to solve the technical problem that it is difficult to accurately evaluate the microstructure evolution and interface bonding strength of the existing multi-dimensional network ceramic coating and polyethylene-based film composite diaphragm under harsh working conditions such as high temperature and long-term circulation, thereby failing to meet the requirements of high safety and high performance.
[0005] A first aspect of the present invention provides a method for detecting a lithium ion battery separator, the method comprising: Perform multi-stage wetting test on the diaphragm using at least two test solutions with different viscosities to obtain permeability data and determine the wetting hysteresis region; Applying periodic heat pulse detection to the wetting hysteresis area to obtain temperature-time curve data and determine the abnormal heat diffusion area; Performing temperature-wetting alternating cycle detection on the abnormal thermal diffusion area to obtain strain data and determine the microstructure change area; Performing load-displacement detection on the microstructure change area, obtaining interface binding energy data and pore resistance data and determining the structural failure area; The diaphragm is divided into risk level zones based on the structural failure areas to form application scenario adaptability assessment data.
[0006] Preferably, the method of performing multi-stage wetting detection on the diaphragm using at least two test solutions with different viscosities to obtain transmittance data and determine the wetting hysteresis region includes: According to the pore size range of the multi-dimensional network ceramic coating of the diaphragm and the hydrophilic and hydrophobic properties of the polyethylene-based film of the diaphragm, two test solutions with different surface tensions are prepared; Using a test solution with a lower viscosity among the test solutions to perform a first infiltration test on the multi-dimensional network ceramic coating of the diaphragm to obtain the network pore transmittance distribution data at a first infiltration time point; Performing a second infiltration test on the diaphragm using a test solution with a higher viscosity among the test solutions to obtain network pore transmittance distribution data at a second infiltration time point; The network pore transmittance distribution data at the first infiltration time point is compared with the network pore transmittance distribution data at the second infiltration time point to determine the wetting hysteresis region of the diaphragm.
[0007] Preferably, according to the pore size range of the multi-dimensional network ceramic coating of the diaphragm and the hydrophilic and hydrophobic properties of the polyethylene-based film of the diaphragm, two test solutions with different surface tensions are prepared, including: Acquire pore size distribution data of the main pores and the branch pores in the multi-dimensional network ceramic coating, wherein the pore size of the main pore is greater than 0.5 μm and less than or equal to 2 μm, and the pore size of the branch pore is greater than 0.1 μm and less than or equal to 0.5 μm; A polar organic solvent and a non-polar organic solvent are selected according to the pore size distribution data of the main pore channel and the branch pore channel, wherein the molecular size of the polar organic solvent is smaller than the minimum pore size of the branch pore channel, and the molecular size of the non-polar organic solvent is larger than the minimum pore size of the branch pore channel and smaller than the minimum pore size of the main pore channel; Adding hydroxyl-modified nano-alumina particles to the polar organic solvent and the non-polar organic solvent respectively for modification, wherein the particle size of the nano-alumina particles is 5 nm to 20 nm; The modified polar organic solvent and the non-polar organic solvent are mixed with surfactants respectively to prepare two test solutions with different surface tensions.
[0008] Preferably, the step of applying periodic heat pulse detection to the wetting hysteresis area, acquiring temperature-time curve data and determining the abnormal heat diffusion area includes: Applying heat pulse treatment to the interface between the multi-dimensional network ceramic coating and the polyethylene-based film in the wetting hysteresis region; Acquire temperature rise curve data of the interface during the heat pulse loading stage; Acquire temperature decay curve data of the interface during the thermal pulse unloading stage; The abnormal thermal diffusion area at the interface between the multi-dimensional network ceramic coating and the polyethylene-based film is determined based on the temperature rise curve data and the temperature decay curve data.
[0009] Preferably, the determining of the abnormal thermal diffusion area at the interface between the multi-dimensional network ceramic coating and the polyethylene-based film based on the temperature rise curve data and the temperature decay curve data comprises: Dividing the interface region into a fast thermal response region and a slow thermal response region according to a temperature mutation point in the temperature rise curve data; Extracting a heat retention characteristic region from the temperature decay curve data, wherein the temperature decay rate of the heat retention characteristic region is smaller than the temperature decay rate of the surrounding region; Comparing the spatial distribution overlap between the thermal response hysteresis zone and the heat retention characteristic zone, the region with a spatial distribution overlap greater than 80% is determined as the abnormal thermal diffusion region at the interface between the multi-dimensional network ceramic coating and the polyethylene-based film. Preferably, the method of performing temperature-wetting alternating cycle detection on the abnormal thermal diffusion area, obtaining strain data and determining the microstructure change area includes: Performing temperature cycle treatment on the multi-dimensional network ceramic coating corresponding to the abnormal thermal diffusion region, with the temperature range being 50° C. to 120° C.; During the temperature cycle treatment, a simulated electrolyte is introduced into the pore network of the multi-dimensional network ceramic coating for infiltration; Acquiring pore structure deformation data of the multi-dimensional network ceramic coating during the temperature-wetting alternating cycle; The microstructure change region of the multi-dimensional network ceramic coating is determined according to the pore structure deformation data.
[0010] Preferably, the step of introducing a simulated electrolyte into the pore network of the multi-dimensional network ceramic coating for infiltration during the temperature cycle treatment comprises: A mixed solution of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is prepared as a simulated electrolyte, wherein the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:1:1; The temperature cycle treatment process includes a heating stage and a cooling stage, wherein the temperature range of the heating stage is 50°C to 120°C, the heating rate is 2°C / min, and the temperature range of the cooling stage is 120°C to 50°C, the cooling rate is 1°C / min; In the heating stage, 0.2 mL of the simulated electrolyte is introduced into the pore network of the multi-dimensional network ceramic coating for every 10° C. heating; In the cooling stage, 0.1 mL of the simulated electrolyte is introduced into the pore network of the multi-dimensional network ceramic coating every time the temperature drops by 20°C; During the entire temperature cycle treatment process, the cumulative amount of the simulated electrolyte introduced was controlled not to exceed 2 mL.
[0011] Preferably, the load-displacement detection is performed on the microstructure change area to obtain interface binding energy data and pore resistance data and determine the structural failure area, including: Applying a nano load to the interface between the multi-dimensional network ceramic coating and the polyethylene-based film at the detection position where the microstructure change region is located, and obtaining interface displacement-load curve data; Calculating the interface binding energy data between the multi-dimensional network ceramic coating and the polyethylene-based film at the detection position based on the interface displacement-load curve data; Acquiring pore resistance distribution data along the pore network direction of the multi-dimensional network ceramic coating at the detection position; The structural failure area of the multi-dimensional network ceramic coating at the detection position is determined according to the interface binding energy data and the pore resistance distribution data.
[0012] Preferably, the risk level partitioning of the diaphragm based on the structural failure area to form application scenario adaptability assessment data includes: Acquire pore network damage rate data of the structural failure area; Obtaining energy attenuation rate data of the interface between the multi-dimensional network ceramic coating and the polyethylene-based film corresponding to the structural failure area; Performing risk level assessment on the diaphragm according to the pore network damage rate data and the interface energy attenuation rate data; Based on the risk level assessment result, the application scenario suitability assessment data of the diaphragm in a temperature environment of 50° C. to 120° C. is generated.
[0013] The detection method of the present invention solves the technical difficulties of evaluating the microstructural stability and interface bonding firmness of composite diaphragms in high temperature and long-term cycle environments from multiple levels. First, the method conducts a preliminary screening of the pore structure of the diaphragm through a multi-stage infiltration test, using solutions of different viscosities to infiltrate into the pores of the diaphragm in a graded manner. High-viscosity solutions penetrate more slowly, while low-viscosity solutions can quickly penetrate unobstructed pores. By observing the differences in solution infiltration, it is possible to accurately identify whether local pores are blocked or abnormal. This step effectively solves the shortcoming that existing methods cannot deeply detect changes in the microstructure of composite diaphragms. Through the infiltration characteristics of multiple solutions, it is possible to more sensitively capture heterogeneity and potential inherent defects.
[0014] Next, the method applies periodic heat pulse loading to the identified abnormal area, combined with thermal response analysis, to further detect the interfacial thermal diffusion characteristics of the diaphragm. Traditional thermal stability tests are mostly static measurements, but the present invention uses a heat pulse method to reveal the uneven thermal diffusion phenomenon of the diaphragm interface or pores in a short period of time, which is crucial for determining whether there are microcracks on the interface, whether the pores have collapsed, and other issues. This process effectively identifies the risk of interface failure of the diaphragm under different temperatures and stresses, and provides a clear direction for subsequent in-depth analysis.
[0015] Subsequently, the method applies multiple stresses through alternating cycles of temperature and immersion to simulate the thermal-humidity environmental changes of the diaphragm during battery operation. Each round of alternating cycles accelerates the fatigue evolution of the pores in the coating, helping to detect its degradation trend in real application scenarios. This step more comprehensively reflects the microstructural changes of the diaphragm during thermal expansion and contraction and liquid immersion and drying through long-term cyclic simulation, making up for the deficiency of traditional testing that cannot simulate actual environmental pressure.
[0016] Finally, the nanoscale load-displacement test conducted a detailed analysis of the microstructural change area and further quantified the interface binding energy and pore resistance. This high-precision test can determine the stability of the diaphragm interface at the microscopic level and identify possible structural failure areas. These steps combined accurately reflect the microstructural changes and aging mechanisms of the composite diaphragm under different stress conditions, effectively solving the problem that traditional detection methods are difficult to accurately characterize the stability of the composite diaphragm under high temperature and long-term cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0018] Figure 1 Schematic diagram of an embodiment of a method for detecting a lithium-ion battery separator in an embodiment of the present invention.
[0019] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back...), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0022] In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, "and / or" in the full text includes three solutions. Taking A and / or B as an example, it includes technical solution A, technical solution B, and technical solution that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, which must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0023] An embodiment of the present application provides a method for detecting a lithium-ion battery separator. Figure 1 A flow chart of a method for detecting a lithium-ion battery separator provided in one embodiment of the present application. In this embodiment, the method includes: See also Figure 1 , using at least two test solutions of different viscosities to perform multi-stage wetting tests on the diaphragm, obtain permeability data and determine the wetting hysteresis region; In one embodiment of the present invention, the multi-stage wetting test of the diaphragm using at least two test solutions with different viscosities to obtain transmittance data and determine the wetting hysteresis region includes: According to the pore size range of the multi-dimensional network ceramic coating of the diaphragm and the hydrophilic and hydrophobic properties of the polyethylene-based film of the diaphragm, two test solutions with different surface tensions are prepared; Using a test solution with a lower viscosity among the test solutions to perform a first infiltration test on the multi-dimensional network ceramic coating of the diaphragm to obtain the network pore transmittance distribution data at a first infiltration time point; Performing a second infiltration test on the diaphragm using a test solution with a higher viscosity among the test solutions to obtain network pore transmittance distribution data at a second infiltration time point; The network pore transmittance distribution data at the first infiltration time point is compared with the network pore transmittance distribution data at the second infiltration time point to determine the wetting hysteresis region of the diaphragm.
[0024] The following is a detailed description of the steps involved in the above embodiment: In the first step, two solution formulations with obvious differences in viscosity and surface energy are selected by analyzing the pore size range of the multi-dimensional network ceramic coating and the hydrophilic or hydrophobic characteristics of the polyethylene-based membrane. In this process, a rotational viscometer can be used to test the viscosity value, and a contact angle meter or a surface tension meter can be used to evaluate the wetting behavior of the droplets on the polyethylene-based membrane surface, so as to screen suitable solution raw materials (such as one type of polar and one type of non-polar organic liquid), and add surfactants or nanoparticles according to the pore distribution characteristics for regulation. This stage ensures that the two solutions have different permeability to the coating pores, so as to produce sufficient contrast in subsequent wetting tests and distinguish whether the pores are blocked or narrow.
[0025] In the second step, a solution with a lower viscosity is selected to conduct the first infiltration test on the polyethylene-based membrane coated with a multi-dimensional network ceramic structure. At this time, the membrane can be laid flat on an optical table, the solution can be quantitatively added, and the solution infiltration process can be monitored with the help of a high-speed camera system or an optical transmittance analyzer, and the pore transmittance distribution data can be collected at the agreed time point. Since low-viscosity solutions penetrate faster in the multi-dimensional network pores, the test results can often better reflect the connectivity level of the macroscopic channels, and at the same time, a distribution map can be generated in a shorter time, which is convenient for subsequent comparison and analysis. The transmittance data obtained at this stage can show the initial permeability of the coating as a whole under faster penetration conditions.
[0026] In the third step, the same sample is infiltrated again using a solution with a higher viscosity. The fluidity of this solution is relatively poor, and it takes longer to flow into branch channels or smaller paths. During the test, the distribution data of the corresponding time points are still obtained through optical imaging or transmittance measurement equipment. Compared with the previous infiltration, the difficulty of penetration of different channels in a high viscosity environment is more obvious. If there is micropore blockage or the pore structure is too narrow in some areas, the solution penetration will show obvious delay or low transmittance. The data in this step often reflects subtle defects and local structural discontinuities in a more targeted manner.
[0027] In the fourth step, the permeability distribution information under low viscosity solution is compared with the measurement results under high viscosity solution, and the wetting hysteresis area is determined based on the difference at the same time point or in the same detection cycle. If a certain area shows obvious hysteresis or significantly low permeability in a high viscosity infiltration environment, it is determined that the area is a potential risk location that is susceptible to blockage or pore deformation. The results obtained in this process provide intuitive data support for distinguishing normal channels from abnormal areas, and also indicate the object location for subsequent deeper thermal pulse detection or mechanical analysis. Through this multi-viscosity comparison method, the permeability performance and potential weaknesses of the multi-dimensional network ceramic layer can be analyzed in early detection, so as to more comprehensively grasp the microstructural condition of the composite diaphragm.
[0028] In one embodiment of the present invention, two test solutions with different surface tensions are prepared according to the pore size range of the multi-dimensional network ceramic coating of the diaphragm and the hydrophilic and hydrophobic properties of the polyethylene-based film of the diaphragm, including: Acquire pore size distribution data of the main pores and the branch pores in the multi-dimensional network ceramic coating, wherein the pore size of the main pore is greater than 0.5 μm and less than or equal to 2 μm, and the pore size of the branch pore is greater than 0.1 μm and less than or equal to 0.5 μm; A polar organic solvent and a non-polar organic solvent are selected according to the pore size distribution data of the main pore channel and the branch pore channel, wherein the molecular size of the polar organic solvent is smaller than the minimum pore size of the branch pore channel, and the molecular size of the non-polar organic solvent is larger than the minimum pore size of the branch pore channel and smaller than the minimum pore size of the main pore channel; Adding hydroxyl-modified nano-alumina particles to the polar organic solvent and the non-polar organic solvent respectively for modification, wherein the particle size of the nano-alumina particles is 5 nm to 20 nm; The modified polar organic solvent and the non-polar organic solvent are mixed with surfactants respectively to prepare two test solutions with different surface tensions.
[0029] The following is a detailed description of the steps involved in the above embodiment: In the first step, common microscopic tests and gas adsorption methods can be used to quantify the size distribution of main and branch channels in multi-dimensional network ceramic coatings. For different channels with pore sizes above or below 0.5µm, field emission scanning electron microscopy combined with image analysis software or gas adsorption-desorption instrument can be used to measure the pore size distribution curve, and multi-point data collection can be performed on the cross section or surface of the coating sample. This can distinguish the proportion of larger channels and finer channels, providing a quantitative basis for subsequent solvent molecule size matching.
[0030] In the second step, based on the pore size range measured in the previous step, select polar organic solvents that can adapt to smaller channels and non-polar organic solvents that can adapt to larger channels. Polar organic solvents can be selected from acetone or acetonitrile, etc., and the molecular size is smaller than the minimum pore size of the branch channel, which is convenient for penetrating into smaller areas; non-polar organic solvents can be selected from n-hexane or cyclohexane, etc., and the molecular size must be larger than the minimum pore size of the branch channel but smaller than the minimum pore size of the main channel. Through this targeted solvent combination, the degree of penetration of pores of different sizes can be more accurately evaluated with the help of differentiated molecular penetration behavior.
[0031] In the third step, hydroxyl-modified nano-alumina particles are added to polar organic solvents and non-polar organic solvents respectively, and the particle size is controlled between 5nm and 20nm. Ultrasonic dispersion or planetary agitator can be used to fully mix the nanoparticles and the solvent to make them in close contact, so as to enhance the solution's ability to wet the coating surface and the change in interfacial energy. This process uses the surface hydroxyl modification of nanoparticles to make the two solutions show a more distinct difference in penetration behavior, which is convenient for extracting the pore characteristics inside the multidimensional network during the detection process.
[0032] In the fourth step, the modified polar and non-polar solvents are mixed with surfactants to obtain two test solutions with significantly different surface tensions and viscosities. For the addition of surfactants, anionic or non-ionic products can be used, and the solution can be uniform at a moderate stirring rate. The solution combination obtained in this way can be used to infiltrate the main pores and branch pores in steps during subsequent applications, and by comparing the differences in penetration time and infiltration depth, possible blockage areas or local structural weaknesses can be identified, thereby effectively improving the resolution and sensitivity of the detection.
[0033] Please continue reading Figure 1 , applying periodic heat pulse detection to the wetting hysteresis area, obtaining temperature-time curve data and determining the abnormal heat diffusion area; In one embodiment of the present invention, applying periodic heat pulse detection to the wetting hysteresis area, acquiring temperature-time curve data and determining the abnormal heat diffusion area includes: Applying heat pulse treatment to the interface between the multi-dimensional network ceramic coating and the polyethylene-based film in the wetting hysteresis region; Acquire temperature rise curve data of the interface during the heat pulse loading stage; Acquire temperature decay curve data of the interface during the thermal pulse unloading stage; The abnormal thermal diffusion area at the interface between the multi-dimensional network ceramic coating and the polyethylene-based film is determined based on the temperature rise curve data and the temperature decay curve data.
[0034] The following is a detailed description of the steps involved in the above embodiment: In the first step, a pulse heating device such as a laser or infrared lamp can be used to directly input short-term, high-intensity heat to the interface between the multi-dimensional network ceramic coating and the polyethylene-based film in a wetting hysteresis state. The power and time interval of the pulse can be adjusted according to the detection requirements to produce a significant temperature gradient at the interface and avoid overall overheating. This operation can quickly trigger the heat diffusion process in a local area, laying the foundation for the subsequent acquisition of temperature signals. In this way, short-term heat shocks are more likely to highlight the thermal resistance differences caused by microcracks or pores.
[0035] In the second step, while pulse heat is applied to the interface, infrared thermal imaging or high-speed temperature sensors are used to record the temperature rise curve during the heating phase. High-speed acquisition mode is usually used for recording in order to capture the entire process from ambient temperature to the predetermined peak value. If there are stratification or local voids in the interface structure, the efficiency of heat transfer to the base film or ceramic particles will show an obvious timing delay or temperature platform on the curve. This method of synchronous loading and measurement can more accurately locate the initial heat diffusion rate in the local area.
[0036] In the third step, after removing or turning off the heat source, the same temperature monitoring device is used to continue tracking the process of the interface falling from the peak temperature to the ambient temperature. The temperature decay curve obtained at this stage is particularly critical for evaluating the heat dissipation capacity of the material and the interface bonding condition. If there are microcracks or local cavities in the local area, the heat retention will be significantly prolonged; if the interface is uniform and tight as a whole, the temperature will decay evenly to a stable level. The measurement results of this process can be used to further determine the stability of the coating and base film under the influence of external stress.
[0037] In the fourth step, the temperature rise data obtained during the heating phase is compared with the temperature drop data obtained after unloading to confirm whether there is obvious non-uniform heat dissipation or abnormal temperature delay area. If the two sets of data show a large deviation in the local space, it can be determined as the abnormal location of heat diffusion. This step can effectively identify potential microcracks or poor bonding areas at the interface between the multi-dimensional network ceramic coating and the polyethylene-based film, which will help to further analyze whether these abnormal points will cause more serious failures.
[0038] In one embodiment of the present invention, the determining of the abnormal thermal diffusion area at the interface between the multi-dimensional network ceramic coating and the polyethylene-based film based on the temperature rise curve data and the temperature decay curve data comprises: Dividing the interface region into a fast thermal response region and a slow thermal response region according to a temperature mutation point in the temperature rise curve data; Extracting a heat retention characteristic region from the temperature decay curve data, wherein the temperature decay rate of the heat retention characteristic region is smaller than the temperature decay rate of the surrounding region; By comparing the spatial distribution overlap of the thermal response hysteresis zone and the heat retention characteristic zone, the region with a spatial distribution overlap greater than 80% is determined to be the abnormal thermal diffusion region at the interface of the multi-dimensional network ceramic coating and the polyethylene-based film.
[0039] The following is a detailed description of the steps involved in the above embodiment: In the first step, infrared thermal imaging equipment or high-sensitivity temperature sensors can be used to obtain a curve of the interface temperature rising over time, and data processing software can be used to monitor the temperature changes at each sampling point. Set a threshold or calculate the temperature rise slope. When the temperature of a certain area jumps significantly at the beginning of pulse loading, it can be identified as a partition with fast heat transfer; and those partitions with slow heating or flat curves are judged as lagging thermal response parts. In this way, it is possible to distinguish which part of the overall interface responds quickly to the pulse heat flow and which part has heat transfer obstacles.
[0040] In the second step, the same detection device can be used to record the interface temperature decay curve over time after stopping or turning off the heat source, and the analysis can be performed on each sampling area. If certain locations maintain a high temperature at a lower decay rate during the cooling process, it means that heat is more likely to be retained there. Here, the slope of the decay curve can be extracted or the temperature drop within the same time period can be compared to determine whether there are possible micro-voids or interface defects. This approach can accurately identify areas where there is still a significant temperature retention phenomenon during the heat pulse unloading stage.
[0041] In the third step, the spatial position of the part determined as hysteresis in the first stage is compared with the heat retention partition identified in the second stage. Image registration or pixel overlap algorithm can be used to calculate the overlap ratio of the two types of abnormal partitions in coordinates. If this overlap value exceeds the agreed threshold (for example, 80%), the contiguous area can be identified as a part with a high probability of abnormal heat diffusion. Through this multi-angle cross-analysis method, the range of uneven interface thermal conductivity can be clearly screened out, providing highly targeted temperature distribution information for judging the combination of multi-dimensional network ceramic coating and polyethylene-based film.
[0042] Please continue reading Figure 1 , performing temperature-wetting alternating cycle detection on the abnormal thermal diffusion area, obtaining strain data and determining the microstructural change area; In one embodiment of the present invention, the step of performing temperature-wetting alternating cycle detection on the abnormal thermal diffusion region, acquiring strain data and determining the microstructure change region includes: Performing temperature cycle treatment on the multi-dimensional network ceramic coating corresponding to the abnormal thermal diffusion region, with the temperature range being 50° C. to 120° C.; During the temperature cycle treatment, a simulated electrolyte is introduced into the pore network of the multi-dimensional network ceramic coating for infiltration; Acquiring pore structure deformation data of the multi-dimensional network ceramic coating during the temperature-wetting alternating cycle; The microstructure change region of the multi-dimensional network ceramic coating is determined according to the pore structure deformation data.
[0043] The following is a detailed description of the steps involved in the above embodiment: In the first step, the implementation of temperature cycling treatment can be achieved through a temperature control box or a heating platform. The equipment can accurately control the temperature in the range of 50°C to 120°C. The sample needs to undergo a certain period of heating and cooling cycles in this process to simulate the alternation of high and low temperature environments that may occur in actual use. The frequency and rate of temperature fluctuations need to be set to conform to the actual temperature change characteristics of the battery under working conditions. Usually, a heating rate of 2°C / min and a cooling rate of 1°C / min can be used to ensure the effectiveness and realism of the test. The main purpose of this stage is to simulate the temperature changes that the multi-dimensional network ceramic coating may encounter during battery operation and observe its impact on material properties.
[0044] In the second step, a simulated electrolyte is introduced into the pore network of the ceramic coating during the temperature cycling treatment, and the working state of the battery is simulated by controlling the amount of liquid and the frequency of introduction during the infiltration process. The formula of the simulated electrolyte can use common electrolyte components, such as a mixed solution of ethylene carbonate and dimethyl carbonate, to ensure good compatibility with the pore structure in the ceramic coating. When introducing the simulated electrolyte, the liquid should be evenly distributed, and the coating should be repeatedly subjected to the infiltration and evaporation process of the liquid by controlling the changes in temperature and humidity. In this process, the pore network of the ceramic coating will be subjected to the dual effects of heat and liquid, thereby verifying the durability and stability of the coating in actual use.
[0045] In the third step, during the alternating cycles of temperature and infiltration, the pores of the multi-dimensional network ceramic coating are monitored in real time using equipment such as electron microscopes or scanning probe microscopes to collect the structural deformation data of the pores. These data can be used to quantify the degree of deformation of the pores, including the expansion, contraction, or generation of internal cracks in the pores, through image analysis software. Through these image analysis techniques, the dynamic changes in the microstructure of the coating can be obtained, providing a quantitative basis for understanding the structural evolution of the ceramic coating during long-term use. The data after each round of temperature change and infiltration cycle can be used to evaluate whether the coating structure is stable and whether there are permanent changes in microcracks or pores.
[0046] In the fourth step, by analyzing the obtained pore structure deformation data and combining the effects of simulated electrolyte and temperature cycles on the coating, the microstructural change areas of the coating can be accurately identified. Specifically, when analyzing the data, attention should be paid to changes in pore morphology, changes in porosity, and possible failure modes such as cracks. Through these analyses, it can be determined which areas have undergone significant structural changes and which areas have maintained good stability. This process helps to further screen out the weaknesses of the multi-dimensional network ceramic coating under the repeated action of high temperature and electrolyte, and evaluate its actual performance under different environmental conditions.
[0047] In one embodiment of the present invention, the step of introducing a simulated electrolyte into the pore network of the multi-dimensional network ceramic coating for infiltration during the temperature cycle treatment comprises: A mixed solution of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is prepared as a simulated electrolyte, wherein the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:1:1; The temperature cycle treatment process includes a heating stage and a cooling stage, wherein the temperature range of the heating stage is 50°C to 120°C, the heating rate is 2°C / min, and the temperature range of the cooling stage is 120°C to 50°C, the cooling rate is 1°C / min; In the heating stage, 0.2 mL of the simulated electrolyte is introduced into the pore network of the multi-dimensional network ceramic coating for every 10° C. heating; In the cooling stage, 0.1 mL of the simulated electrolyte is introduced into the pore network of the multi-dimensional network ceramic coating every time the temperature drops by 20°C; During the entire temperature cycle treatment process, the cumulative amount of the simulated electrolyte introduced was controlled not to exceed 2 mL.
[0048] The following is a detailed description of the steps involved in the above embodiment: In the first step, when preparing a solution simulating an electrolyte, it is first necessary to accurately weigh each solvent according to the ratio (the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:1:1). In order to ensure the uniformity of the solution, a magnetic stirrer can be used to stir and keep the solution uniformly mixed at room temperature. The selection of the three solvents is based on their common physicochemical properties in battery applications. Ethylene carbonate and dimethyl carbonate are typical electrolyte solvents, while the addition of ethyl methyl carbonate helps to adjust the viscosity and stability of the electrolyte. This mixed solution can better simulate the electrolyte properties in actual battery operation in simulation experiments, ensuring that the test conditions are highly consistent with the actual battery use environment.
[0049] In the second step, during the temperature cycle treatment, it is first necessary to set the temperature range of the heating and cooling stages through a constant temperature bath or temperature control box. The temperature range of the heating stage is 50℃ to 120℃, the heating rate is 2℃ / min, and the temperature range of the cooling stage is 120℃ to 50℃, and the cooling rate is 1℃ / min. The purpose of setting this heating and cooling program is to simulate the temperature changes that may occur in the battery during operation. By precisely controlling the rate of temperature change, it can be ensured that the test process is not disturbed by the external environment and the accuracy of the test data is guaranteed. In the experiment, the accuracy of temperature changes can be achieved by installing high-precision temperature sensors to record and control temperature fluctuations at each stage.
[0050] In the third step, 0.2 mL of simulated electrolyte needs to be introduced into the pore network of the ceramic coating for every 10°C increase in temperature. To achieve this process, a microinjection pump can be used to precisely control the amount of electrolyte injected to ensure the consistency of each injection amount. The purpose of liquid introduction is to simulate the contact between the electrolyte and the pore network of the ceramic coating when the battery is working, and to observe the changes in the pore structure of the coating under this environment. Control of the injection amount is crucial to maintaining the consistency and comparability of experimental conditions. This step is expected to effectively simulate the situation where the electrolyte enters the pores of the diaphragm and reacts with the material under actual working conditions of the battery, thereby evaluating the wettability and stability of the pores.
[0051] In the fourth step, during the cooling stage, 0.1 mL of simulated electrolyte was introduced into the pore network of the ceramic coating every time the temperature dropped by 20°C. By adjusting the amount of electrolyte introduced during the cooling process, it can be ensured that the experiment can also simulate the changes in the electrolyte and the dynamic behavior of the pore network during actual use during the cooling process. The reduction in injection volume compared to the heating stage helps to simulate the slow evaporation or drying process of the electrolyte, which is consistent with the consumption or changes of the electrolyte after the battery is operated at high temperature. The implementation of this process can help analyze the microscopic changes in the coating pores under the action of temperature changes and alternating electrolytes, ensuring that the entire process conforms to the multiple stress effects in the actual operation of the battery.
[0052] Finally, during the entire temperature cycle, the total amount of simulated electrolyte introduced was strictly controlled within 2 mL. This total amount control is to simulate the long-term use and consumption of the electrolyte in the battery, ensure the repeatability and accuracy of the experimental results, and avoid unnecessary interference caused by excessive introduction of electrolyte. Through this control strategy, it can be ensured that the amount of solution introduced in each experiment meets the actual application while not affecting the long-term stability of the coating and its performance evaluation.
[0053] Please continue reading Figure 1 , performing load-displacement detection on the microstructure change area, obtaining interface binding energy data and pore resistance data and determining the structural failure area; In one embodiment of the present invention, the load-displacement detection is performed on the microstructure change area, the interface binding energy data and the pore resistance data are obtained, and the structural failure area is determined, including: Applying a nano load to the interface between the multi-dimensional network ceramic coating and the polyethylene-based film at the detection position where the microstructure change region is located, and obtaining interface displacement-load curve data; Calculating the interface binding energy data between the multi-dimensional network ceramic coating and the polyethylene-based film at the detection position based on the interface displacement-load curve data; Acquiring pore resistance distribution data along the pore network direction of the multi-dimensional network ceramic coating at the detection position; The structural failure area of the multi-dimensional network ceramic coating at the detection position is determined according to the interface binding energy data and the pore resistance distribution data.
[0054] The following is a detailed description of the steps involved in the above embodiment: In the first step, when applying nano-loads at the detection position of the microstructural change area, instruments such as nano-indenters or nano-scratchers can be used to apply precise loads and record the displacement of the interface. This equipment has high-precision mechanical loading capabilities and can perform precise mechanical tests on very small areas (usually at the nanometer level), providing continuous data on load and displacement. When conducting the test, select an appropriate load rate to avoid the possibility of interface damage due to excessively fast loading. By applying a controlled load at the interface between the ceramic coating and the polyethylene-based film, the bonding strength of the interface can be evaluated and the displacement response can be accurately measured during the loading process. The main purpose of this process is to reveal the elastic and plastic deformation behavior of the interface when subjected to micro-mechanical effects by obtaining displacement-load curve data, thereby evaluating the potential risks of interface bonding strength.
[0055] In the second step, based on the acquired displacement-load curve data, the interface binding energy can be calculated by the slope of the curve and the load-displacement change trend. The binding energy refers to the maximum bonding strength that the two materials at the interface can maintain when subjected to external force. The interface binding energy can be quantitatively calculated based on the characteristics of the elastic recovery section and the plastic section in the displacement-load curve. This calculation usually involves fitting the load-displacement relationship, and the value of the interface binding energy is calculated using the energy absorption interval in the curve. If the interface binding energy value is low, it indicates that the bond between the two is weak and there is a certain risk of peeling or falling off. Therefore, the purpose of this step is to identify and quantify the strength of the interface bond and provide quantitative data on material properties and potential failures.
[0056] In the third step, along the pore network direction of the multi-dimensional network ceramic coating at the detection position, high-resolution surface analysis techniques such as scanning electron microscopy (SEM) or atomic force microscopy (AFM) can be used, combined with mechanical testing or thermal imaging analysis, to obtain the resistance distribution data of the pore network. Scanning electron microscopy can provide us with high-resolution images to help analyze the geometry and layout of the pores, while atomic force microscopy can more accurately characterize the microstructure of local areas. Through these technical means, the width and depth of the pores and possible defects inside them, such as pore blockage and cracks, can be evaluated. The resistance distribution of the pores is closely related to the mechanical properties and ionic conductivity of the coating. This process can help further understand the performance of ceramic coatings under multiple environmental stresses, especially their stability under thermal and mechanical loads.
[0057] In the fourth step, the structural failure area of the multi-dimensional network ceramic coating can be accurately determined through the comprehensive analysis of the interface binding energy and pore resistance distribution data. The interface binding energy provides strength information at the interface, while the pore resistance data reveals whether the pores are unobstructed or blocked. Combining these data, possible failure modes are analyzed to determine which areas are prone to damage or failure due to weak interface bonding or low pore resistance. This process combines the two types of data to more comprehensively evaluate the overall performance of the coating and determine which areas may experience structural failure during long-term high temperature or multiple cycle tests, thereby providing a scientific basis for subsequent design improvements and material selection.
[0058] Please continue reading Figure 1 , based on the structural failure area, the diaphragm is divided into risk level zones to form application scenario adaptability assessment data.
[0059] In one embodiment of the present invention, the risk level partitioning of the diaphragm based on the structural failure area to form application scenario adaptability assessment data includes: Acquire pore network damage rate data of the structural failure area; Obtaining energy attenuation rate data of the interface between the multi-dimensional network ceramic coating and the polyethylene-based film corresponding to the structural failure area; Performing risk level assessment on the diaphragm according to the pore network damage rate data and the interface energy attenuation rate data; Based on the risk level assessment result, the application scenario suitability assessment data of the diaphragm in a temperature environment of 50° C. to 120° C. is generated.
[0060] The following is a detailed description of the steps involved in the above embodiment: In the first step, the process of obtaining pore network damage rate data first requires the use of high-resolution microscopic techniques (such as scanning electron microscopy or high-resolution X-ray tomography) to observe and measure the changes in the pores in the structural failure area. These microscopic techniques can accurately identify whether the pores have cracks, blockages or other forms of damage. After data collection, image processing software is used to analyze the pore morphology and size and calculate the percentage of pore damage. This process can quantitatively express the damage rate of the pore network by evaluating the proportion of damaged area to total pore area. These data help reveal the integrity of the pores in the structural failure area and predict whether the function of these areas will be significantly affected in actual applications.
[0061] In the second step, the interface energy decay rate data can be obtained by using mechanical testing instruments (such as nanoindenters) to measure the energy absorption and energy loss of the interface between the ceramic coating and the polyethylene-based film. By applying a nanometer-level load and recording its displacement response, the energy decay curve of the area can be obtained. By analyzing the changes in the displacement-load curve, the degree of energy loss of the interface under the action of external force can be evaluated. Specifically, the higher the energy decay rate, the weaker the interface bonding, which may lead to detachment or failure. Through these data, the stability of the interface can be quantitatively evaluated, which helps to further determine whether the interface can adapt to long-term mechanical and thermal stresses.
[0062] In the third step, the risk level is assessed based on the pore network damage rate data and the interface energy decay rate data. By combining the damage rate and energy decay rate data, a multi-criteria decision analysis method (such as weighted average method or decision tree method) is used to assess the risk level of the diaphragm. The goal of this process is to determine whether the diaphragm is suitable for long-term use under specific environmental conditions by combining the severity of pore damage and the strength of interface binding energy. For example, in a working environment with high temperature or high mechanical stress, areas with more severe damage and areas with lower binding energy will be marked as high-risk areas. This assessment can provide a reliable prediction basis for the service life and safety of the diaphragm.
[0063] In the fourth step, based on the risk level assessment results, the adaptability assessment data of the diaphragm in the application scenario within the temperature range of 50°C to 120°C is generated. By correlating the assessed risk level with the behavior of the diaphragm under different temperature conditions, an adaptability assessment report is generated. This report can provide detailed guidance for practical applications and help select suitable diaphragm materials and corresponding working conditions. During the evaluation process, a variety of different battery operating modes (such as high-speed charging and discharging, long-term storage, etc.) can be simulated, and the performance of the diaphragm under these modes can be analyzed, and material optimization recommendations can be given based on this. These evaluation results provide a scientific basis for the selection of materials and the adjustment of the use environment in practical applications, ensuring the long-term reliability of the diaphragm in complex environments.
[0064] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for detecting a lithium-ion battery separator, characterized in that: include: Perform multi-stage wetting test on the diaphragm using at least two test solutions with different viscosities to obtain permeability data and determine the wetting hysteresis region; Applying periodic heat pulse detection to the wetting hysteresis area to obtain temperature-time curve data and determine the abnormal heat diffusion area; Performing temperature-wetting alternating cycle detection on the abnormal thermal diffusion area to obtain strain data and determine the microstructure change area; Performing load-displacement detection on the microstructure change area, obtaining interface binding energy data and pore resistance data and determining the structural failure area; The diaphragm is divided into risk level zones based on the structural failure areas to form application scenario adaptability assessment data.
2. The method for detecting a lithium-ion battery separator according to claim 1, characterized in that: The method of using at least two test solutions with different viscosities to perform multi-stage wetting detection on the diaphragm, obtaining permeability data and determining the wetting hysteresis region includes: According to the pore size range of the multi-dimensional network ceramic coating of the diaphragm and the hydrophilic and hydrophobic properties of the polyethylene-based film of the diaphragm, two test solutions with different surface tensions are prepared; Using a test solution with a lower viscosity among the test solutions to perform a first infiltration test on the multi-dimensional network ceramic coating of the diaphragm to obtain the network pore transmittance distribution data at a first infiltration time point; Performing a second infiltration test on the diaphragm using a test solution with a higher viscosity among the test solutions to obtain network pore transmittance distribution data at a second infiltration time point; The network pore transmittance distribution data at the first infiltration time point is compared with the network pore transmittance distribution data at the second infiltration time point to determine the wetting hysteresis region of the diaphragm.
3. The method for detecting a lithium-ion battery separator according to claim 2, characterized in that: According to the pore size range of the multi-dimensional network ceramic coating of the diaphragm and the hydrophilic and hydrophobic properties of the polyethylene-based film of the diaphragm, two test solutions with different surface tensions are prepared, including: Acquire pore size distribution data of the main pores and the branch pores in the multi-dimensional network ceramic coating, wherein the pore size of the main pore is greater than 0.5 μm and less than or equal to 2 μm, and the pore size of the branch pore is greater than 0.1 μm and less than or equal to 0.5 μm; A polar organic solvent and a non-polar organic solvent are selected according to the pore size distribution data of the main pore channel and the branch pore channel, wherein the molecular size of the polar organic solvent is smaller than the minimum pore size of the branch pore channel, and the molecular size of the non-polar organic solvent is larger than the minimum pore size of the branch pore channel and smaller than the minimum pore size of the main pore channel; Adding hydroxyl-modified nano-alumina particles to the polar organic solvent and the non-polar organic solvent respectively for modification, wherein the particle size of the nano-alumina particles is 5 nm to 20 nm; The modified polar organic solvent and the non-polar organic solvent are mixed with surfactants respectively to prepare two test solutions with different surface tensions.
4. The method for detecting a lithium-ion battery separator according to claim 1, characterized in that: The step of applying periodic heat pulse detection to the wetting hysteresis area, acquiring temperature-time curve data and determining the abnormal heat diffusion area includes: Applying heat pulse treatment to the interface between the multi-dimensional network ceramic coating and the polyethylene-based film in the wetting hysteresis region; Acquire temperature rise curve data of the interface during the heat pulse loading stage; Acquire temperature decay curve data of the interface during the thermal pulse unloading stage; The abnormal thermal diffusion area at the interface between the multi-dimensional network ceramic coating and the polyethylene-based film is determined based on the temperature rise curve data and the temperature decay curve data.
5. The method for detecting a lithium-ion battery separator according to claim 4, characterized in that: The determining of the abnormal thermal diffusion area at the interface between the multi-dimensional network ceramic coating and the polyethylene-based film based on the temperature rise curve data and the temperature decay curve data comprises: Dividing the interface region into a fast thermal response region and a slow thermal response region according to the temperature mutation point in the temperature rise curve data; Extracting a heat retention characteristic region from the temperature decay curve data, wherein the temperature decay rate of the heat retention characteristic region is smaller than the temperature decay rate of the surrounding region; By comparing the spatial distribution overlap of the thermal response hysteresis zone and the heat retention characteristic zone, the region with a spatial distribution overlap greater than 80% is determined to be the abnormal thermal diffusion region at the interface of the multi-dimensional network ceramic coating and the polyethylene-based film.
6. The method for detecting a lithium-ion battery separator according to claim 1, characterized in that: The method of performing temperature-wetting alternating cycle detection on the abnormal thermal diffusion area, obtaining strain data and determining the microstructure change area includes: Performing temperature cycle treatment on the multi-dimensional network ceramic coating corresponding to the abnormal thermal diffusion region, with the temperature range being 50° C. to 120° C.; During the temperature cycle treatment, a simulated electrolyte is introduced into the pore network of the multi-dimensional network ceramic coating for infiltration; Acquiring pore structure deformation data of the multi-dimensional network ceramic coating during the temperature-wetting alternating cycle; The microstructure change region of the multi-dimensional network ceramic coating is determined according to the pore structure deformation data.
7. The method for detecting a lithium-ion battery separator according to claim 6, characterized in that: The step of introducing a simulated electrolyte into the pore network of the multi-dimensional network ceramic coating for infiltration during the temperature cycle treatment comprises: A mixed solution of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is prepared as a simulated electrolyte, wherein the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:1:1; The temperature cycle treatment process includes a heating stage and a cooling stage, wherein the temperature range of the heating stage is 50°C to 120°C, the heating rate is 2°C / min, and the temperature range of the cooling stage is 120°C to 50°C, the cooling rate is 1°C / min; In the heating stage, 0.2 mL of the simulated electrolyte is introduced into the pore network of the multi-dimensional network ceramic coating for every 10° C. heating; In the cooling stage, 0.1 mL of the simulated electrolyte is introduced into the pore network of the multi-dimensional network ceramic coating every time the temperature drops by 20°C; During the entire temperature cycle treatment process, the cumulative amount of the simulated electrolyte introduced was controlled not to exceed 2 mL.
8. The method for detecting a lithium-ion battery separator according to claim 1, characterized in that: The method of performing load-displacement detection on the microstructure change area, obtaining interface binding energy data and pore resistance data and determining the structural failure area includes: Applying a nano load to the interface between the multi-dimensional network ceramic coating and the polyethylene-based film at the detection position where the microstructure change region is located, and obtaining interface displacement-load curve data; Calculating the interface binding energy data between the multi-dimensional network ceramic coating and the polyethylene-based film at the detection position based on the interface displacement-load curve data; Acquiring pore resistance distribution data along the pore network direction of the multi-dimensional network ceramic coating at the detection position; The structural failure area of the multi-dimensional network ceramic coating at the detection position is determined according to the interface binding energy data and the pore resistance distribution data.
9. The method for detecting a lithium-ion battery separator according to claim 1, characterized in that: The risk level partitioning of the diaphragm based on the structural failure area to form application scenario adaptability assessment data includes: Acquire pore network damage rate data of the structural failure area; Obtaining energy attenuation rate data of the interface between the multi-dimensional network ceramic coating and the polyethylene-based film corresponding to the structural failure area; Performing risk level assessment on the diaphragm according to the pore network damage rate data and the interface energy attenuation rate data; Based on the risk level assessment results, the application scenario suitability assessment data of the diaphragm in a temperature environment of 50°C to 120°C is generated.